(untitled) (LACCEI, 2024)
The objective of the paper is to analyze the research trends generated on the digital strategies applied in the performance of the supply chain established at a global level during the period 2010-2022, in addition to reviewing their evolution over time and application of the models business in various technologies. As a methodology, a bibliographic review (SLR) was used from the literature published in Scopus databases. Through an exhaustive systematization, 41 articles were selected, classifying them by year of publication, type of quartile, number of citations, and according to the Sustainable Development Goals (SDG). In turn, the VOSviewer software was used to determine the concurrence between the variables. The literature findings reveal that the implementation of technological tools in the supply chain has been generated with a lack of government support, a deficit of trained personnel and a strong traditional management of the supply chain, the main challenges being those problems that Companies face to contribute to the adaptation of technologies in the improvement of processes and thus meet the goals set out in the SDGs and the improvement of the competitive advantages of nations.